The determination of the stability constants binary complexes of alizarin with Ca(II) and Zn(II) by potentiometric and spectrophotometric methods - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2007)
Alizarin, which consists of 1,2 dihydroxyanthraquinone, is the common madder of the anthraquinoid pigment group. It has been used for textiles, food and medicine. The colour of alizarin is light brown and dissociates low in water. It is in the root of Rubia tinctorum plant. The plant is 50-80 cm high and its trunk is cornered, hard and thorny. In the present study a potentiometric titration and spectrophotometric method has been used to determine stability constants for Ca(II) and Zn(II) with alizarin. Stability constants of binary system have been evaluated by the method suggested by Irving-Rossotti procedure. The protonation and acid constants at 25 degrees C have been found as follows: LogK(1)=pK(2)=8,09 LogK(2)=pK(1)=5,91 The conditional formation constants of the formed complexes were calculated and pH ranges through which the complexation occurs were found. Calcium (II)-Alizarin: LogK(1)=4,58 ; K-1=3,80.10(4) Zinc(II)=Alizarin : LogK(1)=11,34 ; K-1=2,19.10(11) LogK(2)=9,04 ; K-2=1,10.10(9) In addition, the conditional constants were calculated as a function of pH. The maximum values of the conditional formation constants were found to be in accordance with the metal ligand complexes formation constants in a given pH region. The mole fraction of complexes were calculated by means of formation constants. The values of stability constants of metal ligand complexes at 25 degrees C are as follows: The ionic strength was kept constant at I= 0,01 with NaClO4. Additionally Ca(II)-Alizarin and Zn(II)-Alizarin complex formation was examined by spectrophotometric method.
Keywords: alizarin; anthraquinone; binary complex; stability constants